In defence of episcopal power : the case of bishop Egas of Viseu - Vilar, Hermínia Vasconcelos (2012)
The memory of D. Egas is unquestionably linked to the production of what is known as the Summa de Libertate Ecclesiastica. Egas was Bishop of Viseu between 1288 and 1313 and seems neither to have enjoyed any position of particular influence withnear the king nor shared royal spheres of influence. On the contrary, however, the perspective contained within the aforementioned document is that of a bishop devoted to the government of his diocese and his legacy. Furthermore, his name and his role are referred to in the negotiations preceding certain agreements defining the relationship between King D. Dinis and the Church in the period that elapsed between the 1380s 1280s and the early years of the 14th century and his name is certainly linked with the writing of a text as important as that of the Summa. This text, providing a reflection on the relationship between royal power and the episcopate, conveys an image of a prelate much more interested in the political circles and much more interventional than an earlier approach had suggested. It is within this context of establishing a balance between these two apparently contradictory viewpoints that this study was undertaken presenting the administration of Bishop Egas as a case study for a broader perspective on relations between episcopates and the king towards the end of the 13th century.